2015
DOI: 10.2527/jas.2015-9221
|View full text |Cite
|
Sign up to set email alerts
|

Temporal plasma vitamin concentrations are altered by fat-soluble vitamin administration in suckling pigs1

Abstract: Piglets are born with purportedly low plasma vitamin D levels. The objective of this study was to investigate the effect of fat-soluble vitamin administration, primarily vitamin D, by different administration routes on plasma vitamin concentrations in suckling pigs. A total of 45 pigs from 5 litters were allotted at birth to 3 treatments within each litter. Pigs were administered 400 IU of α-tocopherol, 40,000 IU of retinyl palmitate, and 40,000 IU of vitamin D at d 1 of age either orally or by i.m. injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
8
4
1
Order By: Relevance
“…Serum 25-OHD 3 concentrations of the pigs in the water group were greater than those in the CON group until d 21 post-administration (p<0.05) and similar at d 28 and 35 of post-administration. This result agrees with Jang et al [ 6 ] who reported that plasma 25-OHD 3 concentrations of suckling piglets increased with vitamin D 3 administration either orally or by IM injection but the injection had greater efficiency to enhance plasma 25-OHD 3 concentrations compared to oral administration. Jang et al [ 5 ] also reported that vitamin D 3 administration to nursery pigs via drinking water from weaning for 14 d increased plasma 25-OHD 3 concentrations at d 14 postweaning.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Serum 25-OHD 3 concentrations of the pigs in the water group were greater than those in the CON group until d 21 post-administration (p<0.05) and similar at d 28 and 35 of post-administration. This result agrees with Jang et al [ 6 ] who reported that plasma 25-OHD 3 concentrations of suckling piglets increased with vitamin D 3 administration either orally or by IM injection but the injection had greater efficiency to enhance plasma 25-OHD 3 concentrations compared to oral administration. Jang et al [ 5 ] also reported that vitamin D 3 administration to nursery pigs via drinking water from weaning for 14 d increased plasma 25-OHD 3 concentrations at d 14 postweaning.…”
Section: Resultssupporting
confidence: 92%
“…In the temporal change of serum 25-OHD 3 concentrations ( Table 4 ), serum values in the injection group reached a peak at d 3 post administration and were reduced afterward which is similar to that reported by Jang et al [ 6 ]. However, this peak day was postponed a day later than from Jang et al [ 6 ] that reported the peak day at d 2 after a single vitamin D 3 injection to newborn pigs with the same amount of vitamin D 3 as used in the current study.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations